Recent advances in the development of commercial axial magnetic field vacuum interrupters - v. Eckroth, K.; Bestel, E.F. (IEEE Transmission and Distribution Conference, 1994, 1994)
Three different vacuum interrupter constructions are discussed. The so called rotating arc interrupter, and two axial magnetic field interrupters are described with attention to the uniformity of the axial field at the contact face. The salient feature of the most recent interrupter is its ability to clear a current density of 1680 A/cm/sup 2/ at the contact face.< >